EXISTING PROBLEMS IN THE MANAGEMENT OF PUBLIC EXTERNAL DEBT AND WAYS TO ELIMINATE THEM (American Journal of Interdisciplinary Research and Development, 2024)
The article covers factors affecting it in improving the management of public debt, controlling budget debt and budget spending, managing public debt. In order to make more effective use of foreign debt in the article, the analysis of its state and practice in the country, as well as the analysis of the practice of foreign countries, to identify the problems that arise in the effective management of State foreign debt